2017
DOI: 10.1038/nm.4415
|View full text |Cite
|
Sign up to set email alerts
|

Targeting glioma stem cells through combined BMI1 and EZH2 inhibition

Abstract: Glioblastomas are lethal cancers defined by angiogenesis and pseudopalisading necrosis. Here, we demonstrate that these histological features are associated with distinct transcriptional programs, with vascular regions showing a proneural profile and hypoxic regions a mesenchymal pattern. As these regions harbor glioma stem cells (GSCs), we investigated the epigenetic regulation of these two niches. Proneural, perivascular GSCs activated EZH2, whereas mesenchymal GSCs in hypoxic regions expressed BMI1 protein,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
318
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 310 publications
(333 citation statements)
references
References 59 publications
(68 reference statements)
15
318
0
Order By: Relevance
“…GBM is characterized by complex tissue heterogeneity, in which there is a class of stem cell-like tumor-initiating cells, called GSCs, which have the ability to self-renew, grow continuously and differentiate into multiple neural cell types [34][35][36]. Further studies found that GSCs are key factors leading to the occurrence, recurrence, treatment tolerance and poor prognosis of glioma [35,[37][38][39][40]. We successfully propagated eight human GSC lines with four different molecular subtypes and found the highest PSAP expression and secretion in mesenchymal GSCs, as determined by western blotting and ELISA.…”
Section: Discussionmentioning
confidence: 99%
“…GBM is characterized by complex tissue heterogeneity, in which there is a class of stem cell-like tumor-initiating cells, called GSCs, which have the ability to self-renew, grow continuously and differentiate into multiple neural cell types [34][35][36]. Further studies found that GSCs are key factors leading to the occurrence, recurrence, treatment tolerance and poor prognosis of glioma [35,[37][38][39][40]. We successfully propagated eight human GSC lines with four different molecular subtypes and found the highest PSAP expression and secretion in mesenchymal GSCs, as determined by western blotting and ELISA.…”
Section: Discussionmentioning
confidence: 99%
“…Widespread epigenetic reprogramming occurs during both stem cell differentiation and malignant transformation (Amente et al ., ). Recent findings indicate that chromatin dysregulation is likely to play a crucial role in GBM and the dependence of GSCs on epigenetic regulators offers an opportunity to target their self‐renewal capacity (Jin et al ., ; Miller et al ., ). Based on prior reports that GSCs are the most aggressive cellular population responsible for glioblastoma recurrence (Bao et al ., ; Rich, ) and the role of numerous KDMs in stem cell maintenance (Amente et al ., ; Andricovich et al ., ; He et al ., , ), we hypothesized specific function of KDM2B in GSCs.…”
Section: Resultsmentioning
confidence: 98%
“…Classifying GBMs into subtypes has focused on genetic signature at the whole‐tumor level, thereby simplifying the substantial intratumoral heterogeneity of GBMs. Independent studies have elucidated the differential gene expression patterns in distinct anatomic regions within a tumor . More specifically, the leading‐edge of GBMs was shown to display a proneural‐like signature, while the tumor core appeared more mesenchymal‐like .…”
Section: Overcoming Tumor Heterogeneitymentioning
confidence: 99%
“…102,103 More specifically, the leading-edge of GBMs was shown to display a proneural-like signature, while the tumor core appeared more mesenchymal-like. 103 The intratumoral heterogeneity of GBMs was further illustrated by cellular and genomic analysis at the single-cell level. Meyer and colleagues profiled individual tumorigenic clones from patient-derived GBM cells, identifying pre-existing clones harboring the potential to resist anti-tumor treatments such as TMZ.…”
Section: Understanding the Heterogeneity Of Brain Tumorsmentioning
confidence: 99%